If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(2x + -3x) = 33 Combine like terms: 2x + -3x = -1x -3(-1x) = 33 Remove parenthesis around (-1x) -3 * -1x = 33 Multiply -3 * -1 3x = 33 Solving 3x = 33 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '3'. x = 11 Simplifying x = 11
| 3/4x7/6 | | 12=18-3x+2x | | 2x^2-25x-6=0 | | 2x^2-(k-1)(k-1)x+k-2=0 | | 7m+8-9+4m= | | 2x^2-(k^2-2k+1)x+k-2=0 | | -4x+8x=36 | | 8-x=-16 | | 2x^2-(k-1)x+k-2=0 | | 3=81/u | | 8x+124=3x+15 | | 10x+5=15+9x-6 | | 63x+3=5x+3 | | 12x=6300 | | 12*63=100x | | 7+1+(-4)-(-7)= | | x+73+(x-11)=90 | | -2-n=-6 | | x+48+(x-44)=90 | | 100=(100+x)*0.0765-x | | 30-v=166 | | -8w-20=4(w-8) | | 4[x+(2-3x)]=2(4+4x) | | 1/(3n^-4) | | 0.35x=10+0.1x | | 1215/9 | | 2/3×6= | | -1333.3333x+21999.996=1000 | | -1333.3333x+21999.996=0 | | F(x)x=1.5 | | x^6-5x^3-8=0 | | 7^3x-4=1/2401 |